PENINGKATAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA KELAS IV MATERI SUMBER ENERGI DENGAN PENERAPAN METODE EKSPERIMEN DAN MEDIA LUDISEN - Devi Alfianti, Christina; Agnes Herlina Dwi Hadiyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was motivated by the low critical thinking ability and learning outcomes of grade IV students at Gemawang Elementary School. This study aims to: (1) describe efforts to improve critical thinking ability and science learning outcomes of class IV energy source materials at SD Negeri Gemawang through the implementation of the experimental method and ludisen media; (2) improving the critical thinking ability of science students in grade IV of SD Gemawang through the application of the experimental method and ludisen media; and (3) improve science learning outcomes of grade IV elementary school student through the application of the experimental method and ludisen media. The type of research used is Classroom Action Research (CAR). The subjects of the study were grade IV students of SD Negeri Gemawang numbering 20 in the 2023/2024 school year. Data collection techniques are obtained by interviews, observations, questionnaires, and tests. The data analysis techniques used are quantitative and qualitative. The results showed; (1) efforts to improving critical thinking ability and learning outcomes of grade IV students of SD Negeri Gemawang using through the experimental method and ludisen media were conducted in several steps, including material explanation, experimental method application, ludisen media implementation, concluding, doing evaluation questions, and reflection; (2) the application of the experimental method and ludisen media could improve students' critical thinking ability;(3) the application of the experimental method and ludisen media could enhance students' science learning outcomes.